PENGARUH AKUNTABILITAS, KEPEMIMPINAN, DAN PARTISIPASI MASYARAKAT TERHADAP EFEKTIVITAS PENGELOLAAN DANA DESA - Ni Made Sriani (Hita Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of accountability, leadership, and community participation on the effectiveness of village fund management in Mengwi District, Badung Regency. The sample of this research is 15 village offices in the District of Mengwi with the number of respondents as many as 90 people. The method of determining the sample using purposive sampling method, data were collected using a questionnaire. Data were analyzed using Multiple Linear Regression analysis. The test results show that accountability has a positive effect on the effectiveness of village fund management. Leadership has a positive effect on the effectiveness of village fund management. Community participation has a positive effect on the effectiveness of village fund management. This shows that the better the accountability, leadership, and community participation, the better the effectiveness of village fund management in Mengwi District, Badung Regency.